TPB Influence on Type 2 Diabetes Coding: Al-Islam H.M. Mawardi Hospital - Puspitasari, Ayu Ferina; Cholifah, Cholifah (Universitas Muhammadiyah Sidoarjo, 2024)
This study applies the Theory of Planned Behavior (TPB) to qualitatively analyze the factors influencing coders' intentions in coding type 2 diabetes mellitus at a general hospital. Conducted from February to July 2023, data were collected through interviews and questionnaires with two outpatient coder officers. Findings indicate that coding background, officer acumen, workload, legibility of doctors' writing, availability of coding resources, data clarity, familial support, peer influence, and environmental factors significantly influence coders' intentions. Moreover, factors such as coder knowledge and experience, as well as opportunities for continuous learning, play pivotal roles. These findings underscore the importance of addressing various determinants to enhance coding accuracy and efficiency, thereby improving healthcare management and resource allocation. Highlights : Coders' intentions in coding T2DM elucidated through TPB analysis. Influential factors include coding background, workload, and availability of resources. Addressing determinants crucial for enhancing coding accuracy and healthcare efficiency. Keywords: TPB analysis, type 2 diabetes mellitus, outpatient coders, coding behavior, healthcare management